(untitled) (Research, Society and Development, 2025)
The present study proposes the application of digital industrial radiography techniques to analyze colored pencils of different formulations, aiming to identify structural and compositional variations associated with X-ray attenuation. This investigation seeks to demonstrate the potential of industrial radiography as both a didactic and scientific tool for the characterization of low-density materials. The images were acquired using an Intecal MAAF radiographic system coupled with a Carestream Direct View Classic CR computed radiography system. The samples were mounted on a 3D-printed support designed in Tinkercad. Radiographic contrast (CR) analysis was performed using ImageJ, comparing internal and external regions of interest within the pencils. Additionally, structural characterization was carried out through X-ray diffraction (BRUKER D2 PHASER). The results revealed significant attenuation variations among the pencils. The “brown spice” sample (IL3) exhibited higher CR values in four of the five boxes, suggesting that its specific formulation directly influences its interaction with radiation. The analysis also indicated heterogeneity among pencils of the same color, later confirmed and quantified by spectroscopy. The ability to detect such differences in low-density materials highlights the potential of industrial radiography for quality control of polymers and composites. Moreover, the distinctive attenuation of the brown spice pigment points to possible applications as a radiopaque marker in medical, forensic, and artifact conservation analyses. Future studies should aim to establish quantitative relationships between composition and attenuation, as well as expand sampling and include manufacturing data to improve quality control strategies.